Film Piracy, Organized Crime, and Terrorism - Treverton, Gregory F (RAND Corporation, 2009)
A study of the involvement of organized-crime and terrorist groups in product counterfeiting. Case studies of film piracy illustrate the problem of criminal--and perhaps terrorist--groups using this new high-payoff, low-risk way to fund their activities. Cooperation among law enforcement and governments worldwide is needed to combat intellectual-property theft, which threatens the global information economy, public safety, and national security.